Adaptação de próteses auditivas em crianças e adolescentes do programa de atenção à saúde auditiva da UFSM - Aurélio, Nilvia Herondina Soares (2010)
PURPOSE: Analyze children and teenagers profile, hearing aids users, assisted by the program of health care hearing of Federal University of Santa Maria (FUSM), in order to verify hearing aid use related aspects, maintenance and therapeutic monitoring, as well as to evaluate the benefits granted by the sound amplification in this group of study. METHODS: 70 individuals with age between 3 and 18 and their relatives took part of the program. For all the individuals was applied an anamnesis with questions relative to the socioeconomic conditions of them; to the developing and school performance of the patient; to the use and maintenance of hearing aids; to the use of resources from the local community to speech language therapy and access to specialists; it was verified the technical conditions of the hearing aids, too. To assess the benefit provided by the hearing aids the Infant Toddler Meaningful Auditory Integration Scale (IT-MAIS) was applied to children under four years old; to children between 04 and 07 years old the Meaningful Auditory Integration Scale (MAIS) was applied; and for the individuals between 08 and 14 years old the benefit questionnaire assessing in children and teenagers proposed by Boscolo et al (2006). RESULTS: 6 preschool (8,6%), 34 children (48,6%) and 30 teenagers (42,9%) were appraised. Almost 40% of the individuals had a profound degree of hearing loss; 91,4% of the individuals possessed families with incomes around 1 to 3 minimum salary; 80% of the individuals attended the elementary school; nearly 80% of the individuals used to utilize efficiently the hearing aids; and around 20% of the individuals found any hearing aids maintenance difficulty on their cities; 55,75 of the individuals received speech- language therapy, but 44,3% did not receive this attendance. Only one individual could be evaluated through IT-MAIS scale, which had punctuation equal to 0 (zero). The MAIS scale was applied to 10 individuals, obtaining a medium punctuation equals to 19,9. By the benefit questionnaire assessing in children and teenagers proposed by Boscolo et al (2006) 52 individuals were assessed, in which it was certified that in all the analyzed items, the positive answers prevailed. CONCLUSION: It was evident that most individuals were located in the age group from 6 to 12 years old, as well as they possessed profound degree sensorineural kind of hearing loss and were part of families with low incomes and possessed a satisfactory school performance. Also, it was verified that most of children and teenagers used to utilize efficiently the hearing aids and the benefit granted by the amplification could be observed in different daily situations, both from the perspective of the patient and his family